TRANSFORMING VISION: LONG TERM FOLLOW-UP OF RIGID GAS PERMEABLE CONTACT LENS THERAPY IN ANISOMETROPIC AMBLYOPIA - Aritonang, Christina; Fauzia, Sarah; Mutiani, Zafirah; Yaacob, Hafiza Izyani; Kamaruddin, Muhammad Irfan (Folia Medica Indonesiana, 2025)
Amblyopia is defined as a unilateral or bilateral reduction in visual acuity resulting from abnormal binocular interaction during the critical period of visual development. Amblyopia is classified into three etiologies: strabismus, refractive amblyopia, and other vision obstructions. Amblyopia refractive is the most common form resulting from the integration of the retina. Amblyopia is most prevalent in childhood, with a global prevalence of 1.44% mainly in Asia, the United States, and Europe. Early detection and treatment are crucial to ensure proper visual development and prevent long-term vision problems. RGP contact lenses are an alternative treatment method that creates a more effective treatment compared to wearing glasses in amblyopia caused by anisometropia. The case series rivet around young adolescents with amblyopia anisometropia, focusing on the use of RGP contact lenses and the great outcome of visual acuity which improve quality of life.